Energy and Productivity Yield Assessment of a Traditional Furnace for Noncentrifugal Brown Sugar (Panela) Production - Luis F. Gutiérrez-Mosquera; Sebastián Arias-Giraldo; Adela M. Ceballos-Peñaloza (International Journal of Chemical Engineering)
Noncentrifugal brown sugar (called panela in Colombia) is a natural sweetener obtained from the extraction, purification, and concentration of sugarcane juices. In this work, energy and productivity yield of a traditional furnace for panela production were evaluated, considering five performance indices. Experimental productions were developed in a pilot plant facility, analyzing furnace gas emissions of furnace and bagasse properties. Mass, energy, and exergy balances were performed. The following indices were obtained from the experimental runs: energy efficiency 12.726 ± 1.091%, exergy efficiency 9.013 ± 0.710%, energy losses through chimney 72.293 ± 11.507%, yield 0.144 ± 0.021 kgpanela/kgbagasse, productivity 7.450 ± 0.520 kgpanela/h, and bagasse consumption 1.258 ± 0.139 kgbagasse consumed/kgbagasse produced. It was found that these outcomes were strongly influenced by excess air and gas circulation velocity through the furnace, which affects the combustion rate and heat transfer between the gases and the juices. Finally, it was concluded that the traditional scheme is inefficient and requires various critical operational adjustments, such as combustion chamber, chimney draft control, and heat exchangers design.